Gender institutionality in trade unionism. The case of a public sector union: Gender institutionality in trade unionism. The case of a public sector union (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
The institutionalisation of the gender agenda is one of the main topics addressed by studies that examine the intersection between trade unionism and gender. This institutionalisation has generally been achieved through the creation of areas within trade unions specifically dedicated to this issue. Although there are studies that report on the existence of these spaces, the characteristics and meanings of this institutionalisation still need to be investigated, taking into account the trajectories, tensions and scope of this type of strategy. That is why this study aims to characterise the gender area of a trade union for state employees. To this end, we will report on the transformations that this area has undergone, the meanings underlying them, and the challenges it faces. To achieve the proposed objective, the methodology used is qualitative, based on semi-structured interviews with key informants and documentary analysis of institutional archives.
Keywords: trade unionism; gender; institutionalisation; public sector